2011
DOI: 10.1089/ten.tea.2008.0346
|View full text |Cite
|
Sign up to set email alerts
|

Positively and Negatively Modulating Cell Adhesion to Type I Collagen Via Peptide Grafting

Abstract: The biophysical interactions between cells and type I collagen are controlled by the level of cell adhesion, which is dictated primarily by the density of ligands on collagen and the density of integrin receptors on cells. The native adhesivity of collagen was modulated by covalently grafting glycine–arginine–glycine–aspartic acid– serine (GRGDS), which includes the bioactive RGD sequence, or glycine–arginine–aspartic acid–glycine–serine (GRDGS), which includes the scrambled RDG sequence, to collagen with the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 62 publications
(71 reference statements)
2
27
1
Order By: Relevance
“…This percentage equates to 130-160 mg of coupled peptide per milliliter collagen matrix, based on the molar ratio of peptide to monomeric type-I bovine collagen fibers. 36 These values are similar to the effective doses administered in solution in previous in vivo nerve regeneration studies. 29,30 Collagen only and functionalized collagen solutions were injected into Conduits either had a porous outer wall denoted by ''P'' or a nonporous outer wall denoted by ''NP.''…”
Section: Preparation Of Collagen and Functionalized Collagensupporting
confidence: 84%
See 1 more Smart Citation
“…This percentage equates to 130-160 mg of coupled peptide per milliliter collagen matrix, based on the molar ratio of peptide to monomeric type-I bovine collagen fibers. 36 These values are similar to the effective doses administered in solution in previous in vivo nerve regeneration studies. 29,30 Collagen only and functionalized collagen solutions were injected into Conduits either had a porous outer wall denoted by ''P'' or a nonporous outer wall denoted by ''NP.''…”
Section: Preparation Of Collagen and Functionalized Collagensupporting
confidence: 84%
“…32 For the functionalized collagen, the peptide mimetic of the m-HNK 33 (FLHTRLFV, MW: 1032.24, synthesized by GenScript) was grafted onto the collagen using EDC chemistry, as described. 32,36 This peptide has been shown to encourage nerve regeneration and axonal targeting. 30,31 Peptide grafting efficiency was measured indirectly by grafting FITC-tagged m-HNK (GenScript) to collagen and comparing the fluorescence intensity of grafted collagen after reconstitution to a standard curve created by admixing fluorescent peptide into collagen solution.…”
Section: Preparation Of Collagen and Functionalized Collagenmentioning
confidence: 99%
“…Peptide sequences were covalently conjugated onto oligomeric type I collagen using the heterobifunctional crosslinker 1-Ethyl-3-(3-dimethylaminopropyl) carbodiimide (EDC) as previously described [24]. Briefly, fetal calf type I collagen (EPC, Owensville, MO) was reconstituted to 3 mg/mL in 0.02N acetic acid to make an oligomeric collagen solution.…”
Section: Methodsmentioning
confidence: 99%
“…In a previous study using this conjugation technique, we confirmed that the resulting grafting efficiency is between 50–60%. Additionally, the grafting process does not significantly change mechanical properties, fiber diameter, or fiber density of the hydrogel [24]. …”
Section: Methodsmentioning
confidence: 99%
“…For the functionalization of titanium implants with RGD-peptides strategies such as simple adsorption (Song et al, 2010) or chemical linking through gold-thiol chemistry (Ferris et al, 1999) or electrodeposited PEG (Oya et al, 2009) have been carried out. In the case of collagen type I, functionalization with this type of biomimetic peptide has been done through chemical procedures such as using thiol or phosphonate anchors (Roessler et al, 2001), periodate activation (Zhang et al, 2005) or hetero-bifunctional coupling agents (Monteiro et al, 2011). To avoid these chemical modifi cations to functionalize ACSs with biomimetic peptides, one approach has been the design of an RGD peptide with the CBD from the vWF (Fig.…”
Section: Improving the Bmp-collagen Systemmentioning
confidence: 99%